Marketing Community Products: Strategies for Economic Empowerment and Social Inclusion - Iwadiah, Iwadiah (Journal Ligundi of Community Service, 2025)
Background. Community-based products often face challenges in market access, limited brand recognition, and lack of sustainable business strategies, which can hinder their potential to contribute to local economic growth. Therefore, implementing targeted marketing strategies is essential not only for increasing sales but also for promoting social inclusion and community empowerment. Purpose. This quantitative study aimed to analyze the effectiveness of various marketing strategies in empowering local communities economically and fostering social inclusion. Specifically, it examined how community product marketing strategies correlate with increased economic participation and inclusion of marginalized groups such as women, youth, and indigenous populations. Method. The study involved a survey of 310 micro and small-scale community product entrepreneurs across three regions in Indonesia. Data were collected using structured questionnaires and analyzed using descriptive statistics and multiple regression analysis to identify significant patterns and impacts of marketing strategies. Results. The findings show that strategies involving digital marketing, product storytelling, and community-based branding significantly contribute to market expansion and income generation. Moreover, marketing approaches that emphasize local culture and involve inclusive participation (e.g., through cooperatives or local training) were strongly associated with improved social inclusion outcomes. Conclusion. This study highlights the critical role of inclusive and adaptive marketing strategies in promoting the sustainability of community products. The insights provide practical implications for NGOs, policymakers, and marketers aiming to strengthen economic empowerment and enhance social cohesion through market-driven community development initiatives.